2011
DOI: 10.1111/j.1460-9592.2011.03573.x
|View full text |Cite
|
Sign up to set email alerts
|

Are you hungry? Are you thirsty? – fasting times in elective outpatient pediatric patients

Abstract: This study shows that children presenting for elective outpatient surgery are suffering from a considerable amount of pre-operative discomfort because of excessive fasting. Strategies to guarantee minimal fasting at hospital admission are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
2
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 17 publications
6
114
2
10
Order By: Relevance
“…31 The fasting period in pediatrics is sometimes prolonged beyond recommendations. Engelhardt et al 31 recently suggested that fasting times are commonly in excess of the recommended guidelines in a study of 1,350 healthy children 2-16 years old. Children are fasting 12 hours from solids instead of 6-8 hours and fasting from fluids for 7 hours instead of 2-4 hours.…”
Section: Prolonged Fasting Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The fasting period in pediatrics is sometimes prolonged beyond recommendations. Engelhardt et al 31 recently suggested that fasting times are commonly in excess of the recommended guidelines in a study of 1,350 healthy children 2-16 years old. Children are fasting 12 hours from solids instead of 6-8 hours and fasting from fluids for 7 hours instead of 2-4 hours.…”
Section: Prolonged Fasting Timesmentioning
confidence: 99%
“…Children are fasting 12 hours from solids instead of 6-8 hours and fasting from fluids for 7 hours instead of 2-4 hours. 31 The fasting times for newborn breastfeeding infants may also exceed the recommended 4-hour period, causing unnecessary hypoglycemia, discomfort, and anxiety.…”
Section: Prolonged Fasting Timesmentioning
confidence: 99%
“…Для дорослих та дітей опубліковані рекомендації Європейського товариства анестезії (European Society of Anaesthesiology, ESA) та Аме-риканського товариства анестезіологів (American Society of Anesthesiologists, ASA), згідно з якими об-меження передопераційного споживання твердої їжі та сумішей для харчування немовлят (дітей до 1 року) становить 6 годин, грудного молока -4 го-дини, пиття прозорих рідин (вода, сік без м'якоті, чай чи кава без молока) -до 2 годин [3,4]. Однак тривалість голодування часто є довшою за реко-мендовану, що створює дискомфорт у більшості пацієнтів і може впливати на газовий склад крові та рівень глікемії ще до операційного втручання [5][6][7].…”
Section: Original Researches оригинальные исследования вступunclassified
“…In addition to being stressful for both children and their caregivers, 4 prolonged fasting times have several negative implications and contribute to poor anesthetic …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Nevertheless, prolonged periods of preoperative fasting are still reported. [3][4][5][6] Data for resource-poor African countries are scarce, 7,8 and long-term audits are lacking. At Queen Elizabeth Central Hospital, which is the largest hospital in Malawi, we identified that preoperative starving times were longer than the standards set by the anesthetic department.…”
Section: Introductionmentioning
confidence: 99%